2018
DOI: 10.17129/botsci.1338
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, growth and phenology of Phalaris minor biotypes resistant to ACCase-inhibiting herbicides in Mexico

Abstract: Background: Herbicide application to control weeds can promote a rapid selection of resistant phenotypes in small geographic areas. Also, in areas with a spatial heterogeneous management, resistance may evolve independently, promoting local adaptation in weeds. In the mexican region known as "El Bajio," 100,000 ha are cultivated with wheat, and the weed Phalaris minor, resistant to ACCase-inhibiting herbicides is commonly present. Question:We aim to identify the population structure of two genes in four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Generalized weed management is not recommended because each farm is a hot spot where the resistant biotypes were selected. Each biotype is locally adapted to its field, and biological traits are synchronized to management practices such as the dates of sowing, physiological maturity, and tillage, among others [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized weed management is not recommended because each farm is a hot spot where the resistant biotypes were selected. Each biotype is locally adapted to its field, and biological traits are synchronized to management practices such as the dates of sowing, physiological maturity, and tillage, among others [9].…”
Section: Discussionmentioning
confidence: 99%
“…To date, resistant populations of Avena fatua, Phalaris minor, and P. paradoxa have been distributed in the Bajio. The first studies of the resistance mechanism in A. fatua and P. minor concluded that mutations in the site of action caused the resistance [8,9]. Among the main factors contributing to the high prevalence of herbicide resistance in the Bajio is farms' large numbers and area.…”
Section: Introductionmentioning
confidence: 99%
“…The net assimilation rate of the biotypes was similar. Additionally, Asp-2078-Gly and Trp-2027-Cys biotypes had a greater leaf area duration due to a higher leaf area, leaf number, and biomass accumulation in leaves [23]. The seed embryo size of the biotypes with the Ile-2041-Asn and Ile-1781-Leu mutations was not statistically different from that of the susceptible biotype, whereas the embryo size was much smaller in the Asp-2078-Gly and Trp-2027-Cys biotypes.…”
Section: Fitness Cost Of Herbicide Resistance In Phalaris Sppmentioning
confidence: 99%
“…These substitutions may occur in one position or more than one position in the ACCase gene, which may confer different resistance patterns among the ACCase inhibitors [67]. Amino acid substitutions leading to resistance to ACCase-inhibiting herbicides in different populations of P. minor have also been identified, including amino acids at 1781 [35,40], 2027 [23,40,41,75], 2041 [23,41], and 2078 [45,51]. In these cases, a substitution rendered ACCase insensitive to graminicides in the resistant P. minor population and conferred different resistance patterns.…”
Section: Resistance To Accase Inhibitorsmentioning
confidence: 99%
“…In both Guanajuato and Bajio región there is not enough informationon richness and diversity of weed plants, most of literature focuses on control and eradication of these plants in crops, so its is promoted. This practice has resulted in persistence of increasingly resistant and competitives pecies such as Phalaris minor (Poaceae), which is a major problem in wheat crops, 12 and wild oat (Avena fatua), which has generated resistance due to continuous herbicide applications. 10,13 Preliminary observations made by the authors suggests a high endemic weed diversity in the Bajio region, that diversity level might be superior than levels reported in studies carried out in agro ecosystems with less production pressure and consequently less technical and of local-traditional use such as the "milpas".…”
Section: Bighead Grass and Removals Of Landmentioning
confidence: 99%